Reprogramming of a defense signaling pathway in rough lemon and sweet orange is a critical element of the early response to 'Candidatus Liberibacter asiaticus'. (29th November 2017) - Yu, Qibin; Chen, Chunxian; Du, Dongliang; Huang, Ming; Yao, Jiqiang; Yu, Fahong; Brlansky, Ronald H; Gmitter, Frederick G
Abstract: Huanglongbing (HLB) in citrus infected by Candidatus Liberibacter asiaticus ( C Las) has caused tremendous losses to the citrus industry. No resistant genotypes have been identified in citrus species or close relatives. Among citrus varieties, rough lemon ( Citrus jambhiri ) has been considered tolerant due to its ability to produce a healthy flush of new growth after infection. The difference between tolerance and susceptibility is often defined by the speed and intensity of a plant's response to a pathogen, especially early defense responses. RNA-seq data were collected from three biological replicates of C Las- and mock-inoculated rough lemon and sweet orange at week 0 and 7 following infection. Functional analysis of the differentially expressed genes (DEGs) indicated that genes involved in the mitogen activated protein kinase (MAPK) signaling pathway were highly upregulated in rough lemon. MAPK induces the transcription of WRKY and other transcription factors which potentially turn on multiple defense-related genes. A Subnetwork Enrichment Analysis further revealed different patterns of regulation of several functional categories, suggesting DEGs with different functions were subjected to reprogramming. In general, the amplitude of the expression of defense-related genes is much greater in rough lemon than in sweet orange. A quantitative disease resistance response may contribute to the durable tolerance level to HLB observed in rough lemon. Abstract : Crop disease: Defending against citrus greening Researchers in the USA have identified genes which help citrus trees cope with the disease Huanglongbing (HLB), or citrus greening. A team led by Frederick Gmitter of the University of Florida, Lake Alfred, sequenced RNA from rough lemon and sweet orange trees seven weeks after infection with HLB. Although no citrus species resistant to HLB are known, rough lemon is tolerant, showing higher survival rates and growing new symptom-free shoots. The team compared the sequence data with a baseline taken at the time of infection to measure how the plants responded to HLB. Many of the same genes were activated in both species, but genetic regulation shifted towards defense in lemon, together with an increase in expression levels, particularly of defense-related genes. These findings offer an overview of an effective early response to HLB.